2(4c-3)=42

Simple and best practice solution for 2(4c-3)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4c-3)=42 equation:


Simplifying
2(4c + -3) = 42

Reorder the terms:
2(-3 + 4c) = 42
(-3 * 2 + 4c * 2) = 42
(-6 + 8c) = 42

Solving
-6 + 8c = 42

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 8c = 42 + 6

Combine like terms: -6 + 6 = 0
0 + 8c = 42 + 6
8c = 42 + 6

Combine like terms: 42 + 6 = 48
8c = 48

Divide each side by '8'.
c = 6

Simplifying
c = 6

See similar equations:

| 7[k-7]=2[11+k] | | (1n+2)(2n+5)=0 | | 14=2a-6 | | -5t^2+40t+60=0 | | x^2+2x^2-125=0 | | 4x^2-40x+45=0 | | 23x-12= | | 0.8x+20-4.5=5+x-0.9x | | 7a+5a=4(a-8)+12(a+9) | | 2(4x-1)+1=20 | | 2n-2=n-8 | | X^2+12x+y^2+4y=60 | | 7y+8=68 | | 6x=333334y | | 10x-7x=84 | | 7y+x=-20 | | 5h+7=3(2h-1) | | X+7y=-20 | | k/2+1=k/3-1 | | x+35+35=180 | | -8=y-6 | | 8(n-3)-(2-n)= | | 5[h+2]=3[j-1] | | 3x(X+1)-3x= | | -9+w=-7 | | 4x+-9+-9y=6 | | -9=u+9 | | .5(100+A)=50 | | x(-53-15x)=0 | | 6+2(3e-1)= | | 29=-2(4x-5)+3(3x+6) | | 2-12x+6=0 |

Equations solver categories